The new challenge in Eastern Europe: Investment and restructuring - Rolf Alter (Intereconomics, 1992)
The reform programmes of most Eastern European countries have liberalized prices and taken on the task of macroeconomic stabilization, but the formation and implementation of structural policies has largely been neglected so far. What steps should the governments of Eastern Europe take to encourage the necessary restructuring of their economies and to attract the urgently needed foreign investment?
Keywords: 330; System Transformation